Tanggung Jawab Pihak Asuransi Terhadap Perjanjian Kredit Bank Dalam Hal Debitur Meninggal Dunia - Ni Putu Purnama Wati; Ni Luh Made Mahendrawati; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Credit agreements are usually accompanied by a collateral agreement and an insurance agreement. This insurance agreement is a means of transferring risk for the bank, especially life insurance in the event of a debtor's death, besides credit can also fall to the heirs if the debtor dies before paying off the remaining credit. This study aims to analyze the legal consequences of the Bank's Credit Agreement in the event that the Debtor dies and to find out the responsibility of the Insurance Party for the Bank's Credit Agreement in the event the Debtor dies. This study uses a normative research method with a statutory approach and a conceptual approach. The results show that the legal consequence of the credit agreement in the event that the debtor dies, there are two possibilities, namely that the credit goes to the heirs as regulated in article 833 of the Civil Code (Burgerlijk Wetboek) or the guarantee is executed by the bank, and the second possibility is that the credit is written off due to a life insurance clause or a life insurance agreement with a banker's clause, which means that the insurance company must be responsible for paying off the remaining debts of the debtor who died according to the terms and conditions of the policy, otherwise the interested party can file a summons to sue the insurance company. From this, the conclusion is that the parties must fully understand the contents of the credit agreement made, so that later if this risk occurs, there will be clarity on the payment of the debtor's remaining debt.